CONSTRUCTING A CHRISTOCENTRIC LIQUID CHURCH: A SYSTEMATIC THEOLOGICAL STUDY OF LIQUID ECCLESIOLOGY ENGAGEMENT WITH HUMANISM IN THE MILLENIAL ERA: KONSTRUKSI LIQUID CHURCH KRISTOSENTRIS: KAJIAN TEOLOGI SISTEMATIKA TENTANG EKLESIOLOGI CAIR DALAM DIALOG DENGAN HUMANISME DI ERA MILENIAL - Firman Simanjuntak; Daniel Simanjuntak (Moriah Theological Seminary, 2026)
AbstractThis paper departs from the phenomenon of increasingly fluid patterns of church attendance, marked by digitalization and demands for cultural relevance. Its main objective is to construct a Christocentric ecclesiology through a critical reading of Pete Ward's concept of the liquid church. Using literature study and systematic theological analysis methods, this research shows that the integration of Christocentric ecclesiology and fluid ecclesiology produces the principle of a church that is “missionary in its fluidity” through digital networks and flexible relationships, but “dense in its Christocentric, doctrine, and sacraments,” so that liquidity does not turn into a spiritual market, but rather becomes a dynamic pilgrimage of faith for the church. This study emphasizes that the church needs to develop contextual theology and ministry models that are firmly rooted in Christ in facing the millennial era. AbstrakTulisan ini berangkat dari fenomena perubahan pola menggereja yang semakin cair, ditandai dengan digitalisasi dan tuntutan relevansi budaya. Tujuan utamanya adalah mengkonstruksi eklesiologi Kristosentris melalui pembacaan kritis terhadap konsep liquid church yang ditawarkan Pete Ward. Dengan menggunakan metode studi literatur dan analisis teologi sistematika, penelitian ini menunjukkan bahwa intergrasi eklesiologi Kristosentris dan eklesiologi cair menghasilkan prinsip gereja yang “cair secara misioner” melalui jejaring digital dan relasi yang flekibel, tetapi “padat secara Kristosentris, doktrinal, dan sakramental,” sehingga likuiditas tidak berubah menjadi pasar rohani, melainkan menjadi dinamika penziarahan iman bagi gereja. Penelitian ini menegaskan bahwa gereja perlu mengembangkan teologi dan model pelayanan yang kontekstual sekaligus berakar kuat kepada Kristus dalam menghadapi era millenial.